GRAPPA 2021 treatment recommendations for psoriatic arthritis - Soriano, ER; Coates, LC; Kavanaugh, A (Journal of Rheumatology, 2023)
At the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) 2022 annual meeting, the recently published new GRAPPA recommendations were presented and their unique characteristics highlighted, including their truly international approach, the inclusion of patient views from the very beginning, the representation by both rheumatologists and dermatologists, consideration of the diverse domains of psoriatic arthritis, and the inclusion of comorbidities to inform possible adverse events and their potential influence on treatment choices.